Women's stereotype threat‐based performance motivation and prepotent inhibitory ability. (24th November 2018) - Hutter, Russell R. C.; Davies, Lucy C.; Sedikides, Constantine; Conner, Mark
Abstract : According to the mere effort account of performance, stereotype threat motivates disproval of the negative performance stereotype, which in turn potentiates the overproduction of prepotent responses. In mathematics (maths), prepotent responding facilitates solve type question (e.g., equations) performance, but reduces comparison type question (e.g., estimations) performance. Problematically, the mere effort account indexes performance motivation as task performance. Also, this account posits that performance reduction on non‐prepotent tasks derives from the overproduction of prepotent responses, as opposed to failed inhibition of prepotent responses associated with the alternative, namely, the working memory interference perspective. We investigated motivational and prepotent responding as applied to stereotype threat. In Experiment 1, a maths question selection task indexed motivation (independently of performance). Stereotype threat led female test takers to select more solve than comparison maths questions, in accord with the mere effort account. In Experiment 2, higher inhibitory ability protected overall maths performance following stereotype threat, but it did not protect non‐prepotentiated comparison question performance (inconsistent with the working memory interference perspective). The results support the mere effort account.